FTIR imaging and HPLC reveal ancient painting and dyeing techniques of molluskan purple - (:unkn) unknown (SPRINGER HEIDELBERG, 2017)
Fourier transform infrared spectroscopy and imaging coupled to optical microscopy, scanning electron microscopy coupled to energy dispersive x-ray spectroscopy and high-performance liquid chromatography (HPLC) coupled to diode-array detection are used to investigate two samples removed from a painted decoration of a burial kline and a textile fragment, both found in Koru tumulus (fifth century BCE) in Daskyleion. Tyrian purple and kaolinite were identified in both samples, thus suggesting that the aluminosilicate compound had an important role in the applied painting and dyeing processes. The textile fragment is composed of undyed cotton and silk yarns dyed with the molluskan dye. The relative compositions of the molluskan materials used in the two archaeological objects are similar and comparable with the corresponding composition measured for a purple sample originated from Murex trunculus mollusks according to the HPLC results. This result is supported by principal component analysis (PCA) which, furthermore, takes into account the relative compositions of the extracts of the three Mediterranean mollusks, published in previous reports.
Keywords: FTIR; Imaging; HPLC; Tyrian purple; Murex; Kaolinite; TYRIAN-PURPLE; ROYAL-PURPLE; IDENTIFICATION; PIGMENT